Design Of a Feeding System with a Capacity Of 3 Tons/Hour at the Npk Plant to Improve Feeding Efficiency and Automation - Zakiyyah Tsuroyyaa; Christianti Christianti; Dhyna Analyes Trirahayu; Harita Nurwahyu Chamidy (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2025)
An NPK plant is a facility that produces NPK fertilizer through a manufacturing process specifically designed to create fertilizer with a special formulation. However, in the production process, the feeding of raw materials is still done manually, resulting in low productivity and high operational costs. Based on production performance tests conducted on September 15, 2024, the manual system only achieved an average of 1.34 tons/hour, or 47% of the production target of 3 tons/hour. Therefore, a transportation system is needed to transport the materials, given the limitations of human labor capacity in terms of material handling and employee safety. This study aims to design an automatic feeding system to maximize production capacity up to 3 tons per hour. The system design begins with analyzing losses due to low productivity of the manual system, analyzing factory requirements, designing the main components of the feeding system, such as the hopper, weigher, and conveyor belt, equipped with an on-off control-based system to ensure consistent raw material flow. Technical design was carried out through visualization using AutoCAD and Visio software, solid flow simulation using Altair EDEM software, and economic feasibility analysis by calculating the Return on Investment (ROI) and Payback Period (POT). The calculation results show that this feeding system has a ROI of 40.8% and a POT of 2.05 years, indicating that the designed system is economically viable for implementation.